2014
DOI: 10.1055/s-0034-1381727
|View full text |Cite
|
Sign up to set email alerts
|

C3–6 Laminoplasty for Cervical Spondylotic Myelopathy Maintains Satisfactory Long-Term Surgical Outcomes

Abstract: Study Design Prospective cohort study. Objective To clarify long-term surgical outcomes of C3–6 laminoplasty preserving muscles attached to the C2 and C7 spinous processes in patients with cervical spondylotic myelopathy (CSM). Methods Twenty patients who underwent C3–6 open-door laminoplasty for CSM and who were followed for 8 to 10 years were included in this study. Myelopathic symptoms were assessed using Japanese Orthopaedic Association (JOA) score. Axial neck pain was graded as severe, moderate, or mild. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 23 publications
2
24
0
Order By: Relevance
“…However, they did not describe the preservation of the muscle attachment at the C2 level in the technique. Conversely, Cho [37] and Sakaura et al [40] preserved the C2 muscle attachment in their technique, and this resulted in lesser loss of cervical lordosis than that reported by Uehara et al [34]. Interestingly, Su et al [36] reported lesser loss of cervical lordosis after performing C3-C6 laminoplasty without preserving the C2 muscle attachment.…”
Section: Radiological Outcomementioning
confidence: 95%
See 4 more Smart Citations
“…However, they did not describe the preservation of the muscle attachment at the C2 level in the technique. Conversely, Cho [37] and Sakaura et al [40] preserved the C2 muscle attachment in their technique, and this resulted in lesser loss of cervical lordosis than that reported by Uehara et al [34]. Interestingly, Su et al [36] reported lesser loss of cervical lordosis after performing C3-C6 laminoplasty without preserving the C2 muscle attachment.…”
Section: Radiological Outcomementioning
confidence: 95%
“…They reported that laminoplasty provided significant enhancement of the JOA score in the short-term, mid-term, and long-term follow-up [34][35][36][37][38][39]. However, Sakaura et al [40] reported that the average JOA score was at its highest point in 12 months of follow-up and decreased slightly to 14.9 in the final follow-up. In this paper [40], they explained that this was due to the non-CSM diseases including lumbar spine canal stenosis, osteoarthritis of knee, carpal tunnel syndrome, and stress urine incontinence.…”
Section: Clinical Outcomementioning
confidence: 97%
See 3 more Smart Citations